(untitled) (The Agriculturists, 2017)
This study was conducted to draw linkage between intake pattern of Choline and nutritional status of pregnant women in 3rd trimester and assess the contribution of agriculture retrospectively to increase its intake. Retrospective data was therefore, collected from United States Development Agency (USDA) data base on Choline content of common vegetable products of Bangladesh. Recommended Choline intake for the pregnant women in 3rd trimester is 450mg/day. The present study conducted using 24 hours recall method revealed that average Choline intake among the study respondents was 317 mg/day which meet 71 percent of the requirement. Majority (72.7%) of the women took Choline below the recommended level (450 mg/day). It is remarkable that 56.7, 55.3 and 52.0% of the pregnant women were deficient in calorie, protein and fat intake respectively. This study found that 54% respondents mothers were within normal Body Mass Index (BMI) while 33% were overweight, 5.3% were underweight and 8.0% were obese. Choline intake status was poor among the pregnant women commencing delivery complication and indicating high prevalence of mental retardation for newborn. The Agriculturists 2016; 14(2) 86-94